The Nitrogen Fixation Characteristics of Terrestrial Nitrogen-Fixing Cyanobacteria and Their Role in Promoting Rice Growth - Lei Wu; Ji Dong; Jian Song; Yuan Zhu; Songhao Che; Xueting Qin; Yufeng Xu; Shiqi Tian; Dongchao Wang; Ping Tian; Xiaoshuang Wei; Xue Yang; et al. (Agronomy)
Cyanobacteria, ubiquitous phototrophic prokaryotes, can enhance soil fertility and crop productivity by promoting biological nitrogen fixation, phosphate dissolution, and mineral release. In this study, five nitrogen-fixing cyanobacteria were isolated and purified from paddy soil in Jilin Province. The effects of nitrogen-fixing cyanobacteria on soil fertility and rice seedling growth were examined through a pot experiment to clarify their growth and nitrogen-fixing characteristics. The results showed that the application of nitrogen-fixing cyanobacteria led to a significant increase in soil nitrogen content. GD2 and GD8 have the highest nitrogenase activity, at 75.33 U·mg−1 and 50.34 U·mg−1, respectively. It also enhanced the activities of urease, sucrase, phosphatase, and catalase in rice soil. In addition, it significantly promoted root development and plant height in rice plants. The total number of microorganisms in rice soil increased by 133–366%. Remarkably, the Desmonostoc muscorum GD2 strain was found to exhibit higher growth state indicators, including the growth curve, chlorophyll content, carbon and nitrogen content, and biomass accumulation, compared to other algae strains. The total nitrogen content of rice leaves treated with GD2 increased by 48.73%, and the soluble protein content increased by 52.89%. GD2 has great potential as an excellent nitrogen-fixing cyanobacteria inoculant for rice, suitable for agricultural production. In conclusion, the application of these nitrogen-fixing cyanobacteria significantly increased soil nitrogen levels and activated key enzyme activities involved in plant nitrogen metabolism. Moreover, it improved nitrogen utilization rates and promoted plant growth.